TEACHER’S PERCEPTION OF BRAIN GYM EXERCISES TO BUILD STUDENTS LEARNING MOTIVATION - Hastuti, Nur Annisa Rini; Siregar, Deasy Yunita (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Motivation is an important factor that influences student success. Teachers' perceptions are needed regarding the phenomenon of decreased learning motivation experienced by students. This study aims to find out about how teachers' perceptions of using Brain Gym to increase student learning motivation and how the results obtained after doing brain gym on student learning concentration. The method used in this study uses a qualitative approach with a descriptive design to provide an overview of teacher perceptions about the use of Brain Gym to build student learning motivation. The researcher conducted interviews to answer the question instruments asked. The interview includes questions, documentation sheets and other supporters. In this study applying convenience sampling, this sampling technique involves people who are easily reached and contacted by researchers. The results showed that almost all teachers have the same opinion that using brain gym can build student learning motivation. Therefore, the use of brain gym can be an example of cool and fun learning. This research has limitations in time and place. So it can be concluded that brain gym has a good effect on student learning motivation, besides helping teachers to be creative in the learning process.